Memahami Keberagaman Pengguna Dalam Pelayanan Perpustakaan Melalui Komunikasi Antar Budaya - Fatmania Diyah Cahyani (IJAL (Indonesian Journal of Academic Librarianship), 2024)
This scientific paper discusses understanding the diversity of users in library services through intercultural communication at the PPM Daarul Huda Putri Banjar Library, MTQ Namira Lamongan, and the Krakahan Tanjung Brebes Village Library, Central Java. How can communication as a librarian be established with library users with the challenges of diversity that occur. Reviewed through intercultural communication and educational background. aims to find out and understand intercultural communication that occurs in libraries between users and librarians, as well as being able to find out and find solutions to the factors that cause obstacles to communication that occurs in libraries. This research uses qualitative descriptive methods and also case studies. With data collection techniques based on observation, interviews and documentation. The results of this research show that to understand the diversity of users in library services, such as in terms of adult age, it is possible to provide a relaxing place to read, several competitions that attract the interest of young children and elementary school children. And in intercultural communication, language diversity can be identified, for example, services such as providing information needed by users can be carried out by equalizing the use of language in communication using the language that unifies the nation, namely Indonesian.